2022
DOI: 10.1097/hjh.0000000000003140
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics of angiotensin II-induced long noncoding and coding RNAs in endothelial cells

Abstract: Objective:Angiotensin II (Ang II)-induced endothelial dysfunction plays an important role in the pathogenesis of cardiovascular diseases such as systemic hypertension, cardiac hypertrophy and atherosclerosis. Recently, long noncoding RNAs (lncRNAs) have been shown to play an essential role in the pathobiology of cardiovascular diseases; however, the effect of Ang II on lncRNAs and coding RNAs expression in endothelial cells has not been evaluated. Accordingly, we sought to evaluate the expression profiles of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…The prevalence of HF has reached 20% at the age of 40, and the incidence increases with age [30]. Previous studies have reported that many aberrantly expressed lncRNAs play a critical role in the pathogenesis and progression of cardiac hypertrophy and myocardial injury [31][32][33]. Yang et al reported that the lncRNA MIAT could affect the handling of calcium and contractile function, resulting in cardiac myocyte remodelling and hypertrophy [11].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of HF has reached 20% at the age of 40, and the incidence increases with age [30]. Previous studies have reported that many aberrantly expressed lncRNAs play a critical role in the pathogenesis and progression of cardiac hypertrophy and myocardial injury [31][32][33]. Yang et al reported that the lncRNA MIAT could affect the handling of calcium and contractile function, resulting in cardiac myocyte remodelling and hypertrophy [11].…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells line the innermost layer of blood vessels and have critical roles in maintaining vascular homeostasis [1]. Imbalanced autophagy can lead to endothelial dysfunction and cardiovascular diseases [2][3][4][5][6]. Autophagy is a tightly regulated process in endothelial cells, and its genetic and epigenetic regulation is well established [3].…”
Section: Introductionmentioning
confidence: 99%
“…AK098656-transgenic rats developed spontaneous hypertension, with increased VSMC synthetic phenotype and narrowed resistant arteries [ 19 ]. On the other hand, studies have also shown that AngII can regulate lncRNAs in ECs, which may, in turn, modulate EC viability, apoptosis, and migration [ 20 , 21 ]. However, it is not yet known whether the perturbation of an endothelial lncRNA can impact BP.…”
Section: Introductionmentioning
confidence: 99%